Shared social responsibility – A concept in search of its political meaning and promise - Offe, Claus (Journal of Public Governance, 2014)
This paper examines the concept of shared social responsibility. The author provides signifi cant theoretical insights on shared social responsibility and its place in democratic theory, especially the liberal theory of justice. This article further explores ways of implementing practically the notion of shared social responsibility into socio-economic policy in order to address the democratic deficit within modern states.